Building a catalogue of foreign literature: reading, evaluating, translating (Altre Modernità, 2024)
How did literature from the Global South arrive in Italy? Adopting the perspective of publishing, this short article focuses on three aspects of the reception of works by writers from former colonies by the Milanese publishing industry in the period 1945-1970. The article focuses in particular on three aspects: (i) the importance of the map of publishing exchanges; (ii) the moment of selection and evaluation of texts to be translated, (iii) the figures of professionals (readers, translators) who composed the 'reading community' of the literatures of the Global South in the period considered.
Keywords: mediation of publishing; Global South; professional reading; translation